Legitimasi dan Legalitas Kekuasaan Eksekutif: Analisis Teoritis terhadap Peraturan Perundang-Undangan tentang Lembaga Kepresidenan dalam Perspektif Hukum Tata Negara Progresif - Firdaus Arifin (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
The strengthening of the Indonesian President's position following the amendments to the 1945 Constitution has reinforced the political legitimacy of the executive; however, it has not been fully accompanied by normative consistency in the institutional relationships between the President, ministries, and ministry-level government agencies. This lack of legal clarity presents challenges to both the principles of legality and legitimacy within the framework of a democratic rule of law. This study aims to analyze the institutional design of executive power based on the principles of progressive constitutional law. Employing normative legal research methods with statutory, case, historical, and comparative approaches, this study examines primary and secondary data related to legislation and constitutional practices. The findings reveal that although the political legitimacy of the President has strengthened, institutional fragmentation and weak regulatory frameworks undermine governmental effectiveness and erode public trust. The study implies the urgent need for normative reform to enhance legal clarity, accountability, and transparency in the exercise of executive power, thereby supporting the consolidation of a just and democratic rule of law.